Aqueous extract of Salvia miltiorrhiza Bunge reduces blood pressure through inhibiting oxidative stress, inflammation and fibrosis of adventitia in primary hypertension - Wu, Ruoyu; Zhou, Yongjie; Xu, Hongjun; Zhao, Wei; Zhou, Luyang; Zhao, Yilin; Cui, Qingzhuo; Ning, Junda; Chen, Hongxu; An, Shengjun (Frontiers in Pharmacology, 2023)
Background: Hypertension is a risk factor for cardiovascular diseases, which is the major cause of mortality worldwide. Previous studies have shown that SABP, a combination of aqueous active ingredient of Salvia Miltiorrhiza DSS, Sal-A, Sal-B and PAL, has a significant antihypertensive effect. However, the underlying mechanisms remain unknown. Objective: This study is to determine the effects of SABP on vascular inflammation, oxidative stress and vascular remodeling of thoracic aorta adventitia in hypertension animal. Also, we will determine the response of the proliferation, differentiation and migration of thoracic aorta adventitia fibroblasts in SHRs to SABP treatment. Methods: SABP or perindopril (positive control) were intraperitoneally injected in SHRs, whose systolic blood pressure was measured by a tail-cuff approach. The effects of SABP on vascular inflammation, oxidative stress, and vascular remodeling in SHRs were investigated by transmission electron microscopy, histochemical staining, and western blot. The adventitial fibroblasts derived from the adventitia of thoracic aorta in SHR and WKY rats were isolated and cultured. CCK8 assay, wound healing method and immunostaining were used to observe the effect of SABP on the proliferation, migration and transformation of fibroblasts into myofibroblasts. Moreover, western blot was applied to detect the proteins related to oxidative stress, inflammation and fibrosis in adventitial fibroblasts. Results: SHRs displayed higher blood pressure with significant vascular remodeling than that observed in WKY rats. The thoracic aorta and adventitial fibroblasts of SHRs exhibited significant oxidative stress, inflammation and fibrosis. SABP treatment repressed oxidative stress, inflammatory reaction and vascular remodeling of thoracic aorta through the ROS/TLR4/NF-κB signaling pathway, and inhibited fibrosis of thoracic aorta in SHR. In addition, SABP inhibited the proliferation and migration of adventitial fibroblasts and their phenotypic transformation to myofibroblasts in vitro through the TGFβ/Smad3 signaling pathway. Conclusion: SABP inhibited the pathological changes of SHRs by ameliorating oxidative stress, inflammation and fibrosis.